Gut Hormones and Their Effect on Bone Metabolism. Potential Drug Therapies in Future Osteoporosis Treatment - Schiellerup, Sine Paasch; Skov-Jeppesen, Kirsa; Windeløv, Johanne Agerlin; Svane, Maria Saur; Holst, Jens Juul; Hartmann, Bolette; Rosenkilde, Mette Marie (Frontiers in Endocrinology, 2019)
Bone homeostasis displays a circadian rhythm with increased resorption during night time as compared to day time; a difference that seems – at least partly – to be caused by food intake during the day. Thus, ingestion of a meal results in a decrease in bone resorption, and people suffering from short bowel syndrome lacks this response. Gut hormones, released in response to a meal, contribute to this link between the gut and bone metabolism. The responsible hormones appear to include the glucose-dependent insulinotropic polypeptide (GIP) and glucagon-like peptide-1 (GLP-1) known as incretin hormones due to their role in regulating glucose homeostasis by enhancing insulin release in response to food intake. They interact with their cognate receptors (GIPR and GLP-1R), both members of the class B G protein-coupled receptors (GPCRs), and already recognized as targets for treatment of metabolic diseases, such as type 2 diabetes mellitus (T2DM) and obesity. Glucagon-like peptide-2 (GLP-2), secreted concomitantly with GLP-1, acting via another class B receptor (GLP-2R), is also part of this so-called gut-bone axis. Several studies, including human studies, have indicated that these three hormones inhibit bone resorption, and moreover that GIP increases bone formation. Another hormone, peptide YY (PYY), is also secreted from the enteroendocrine L-cells (together with GLP-1 and GLP-2) and acts mainly via interaction with the class A GPCR NPY-R2. PYY is best known for its effect on appetite regulation, but recent studies have shown an effect of PYY on bone metabolism. The aim of this review is to summarize the current knowledge of the actions of GIP, GLP-1, GLP-2 and PYY in bone metabolism, and discuss future therapies targeting these receptors for the treatment of osteoporosis.